ENQUETE REALIZADA ACERCA DO CÂNCER NO COLÉGIO TIRADENTES DA BRIGADA MILITAR DE IJUÍ - Bezerra, Luize S.; Oliveira, Daiane D.; Lauter, Dagmar S.; Rosanelli, Cleci L. S. P. (Salão do Conhecimento, 2013)
Resumo